Exhibit at University Libraries Archives and Special Collections: Student of Fire, Paul Gleason, posters - McClelland, Deborah Ann, artist; Colorado State University. Archives and Special Collections, author (Colorado State University. Libraries, 2017)
Posters from a 2017 exhibit and event at Colorado State University Libraries. The event and Archives and Special Collections exhibit showcased the contributions of Paul Gleason to the field of wildland fire science. After retiring from a career as a wildland firefighter, leader, and strategist, Gleason became a faculty member at Colorado State University's Department of Forestry and Natural Resources. He served as an adjunct professor for the Wildland Fire Science program at CSU. Gleason was heavily involved in three significant fires: the Loop Fire in 1966, the Dude Fire in 1990, and the Cerro Grande Fire in 2000.
Student of Fire, Paul Gleason: exhibit at University Libraries Archives and Special Collections, posters
Keywords: Colorado State University; Gleason, Paul; Events; Exhibitions; Wildfires; Fire fighters; Wildfire fighters; Fire fighters